When Is Asia?. Issue 2 (2nd April 2016) - Roy, Ananya
Abstract : Recently, in geography and related disciplines, there has been a call to generate conceptual frameworks from the Global South. Such a call does not imply cataloging the diversity and plurality of the world but rather requires new understandings of relationalities and transformations. In this article, I contribute to these ongoing endeavors by thinking from Asia. In doing so, I interpret Asia not as a bounded geographical location but instead as interconnected space. In particular, I pay attention to how such interconnections reference Asian models of development, thereby creating a politics of futurity. A study of the making of Asian futures allows a broader understanding of the renewal of development in a rearranged south–north world.